Textile-Based Flexible Nanogenerators - Faruk, Ünsal Ömer; Ayşe, Çelik Bedeloğlu; İsmail, Borazan (CRC Press, 2022)
Recently, there has been a great development in the field of smart materials and energy devices. Among many energy devices, nanogenerators that transform waste mechanical energy into electrical energy have attracted considerable research interest in the last 10 years. Polymers with unique characteristics, such as ferroelectric, pyroelectric, piezoelectric, along with flexibility, easy shaping, lightness, and ductility, are frequently used in nanogenerators. The chapter covers recent development in textile-based nanogenerators based on triboelectric, pyroelectric, and piezoelectric mechanisms. Textile-based nanogenerators have previously been proposed for biomechanical energy harvesting for self-powered and low-power electronics. However, with the advancement in nanogenerators, textile-based, human, and environmentally friendly flexible nanogenerators for applications in healthcare monitoring and wearable sensors are drawing attention. This chapter first provides the current state and developments in textile-based nanogenerators and then provides the obstacles and suggestions for the future. © 2022 selection and editorial matter,[Ram K. Gupta, Tuan Anh Nguyen; individual chapters, the contributors.